TN-82 — a relational database management system - Tho, Do Xuan; Thanh, Dinh Thi Ngoc (Journal of Computer Science and Cybernetics, 2015)
Using the relational approach of database systems, the TN-82 has been developed and implemented on a minicomputer. The system consists of four subsystems which have relatively independent functions. These subsystems can be modified and extended, if it is necessary to obtain a new one, which adapts another practical problem with few costs. The system TN-82 is a structured system and  controlled by hierarchical principles. The method based on module programming has been used. Data independence, data consistency, some problems of data security and  integrity are guaranteed. Many blocks of information stored in the system can be unified. The system has been constructed in such a way that the redundant information is  eliminated as much as possible. With a simple but powerful Vietnamese query manguage, a user is able to easily formulate his non-procedural queries.  The query processing is based on implementing in the system of almost operations of relational algebra (such as selection, projection, join, union, difference, intersection). Some problems of query optimizing are resolved and applied in this system, such as analyzing  and choosing the orders of executed operations, selecting access paths,… The system TN-82 can be easily realized on the other more powerful computers.